What lexical decision and naming tell us about reading - Katz, Leonard (2011)
The lexical decision (LD) and naming (NAM) tasks are ubiquitous paradigms that employ printed word identification. They are major tools for investigating how factors like morphology, semantic information, lexical neighborhood and others affect identification. Although use of the tasks is widespread, there has been little research into how performance in LD or NAM relates to reading ability, a deficiency that limits the translation of research with these tasks to the understanding of individual differences in reading. The present research was designed to provide a link from LD and NAM to the specific variables that characterize reading ability (e.g., decoding, sight word recognition, fluency, vocabulary, and comprehension) as well as to important reading-related abilities (phonological awareness and rapid naming). We studied 99 adults with a wide range of reading abilities. LD and NAM strongly predicted individual differences in word identification, less strongly predicted vocabulary size and did not predict comprehension. Fluency was predicted but with differences that depended on the way fluency was defined. Finally, although the tasks did not predict individual differences in rapid naming or phonological awareness, the failures nevertheless assisted in understanding the cognitive mechanisms behind these reading-related abilities. The results demonstrate that LD and NAM are important tools for the study of individual differences in reading.